2000
DOI: 10.1063/1.481146
|View full text |Cite
|
Sign up to set email alerts
|

Proton transfer in the [phenol-NH3]+ system: An experimental and ab initio study

Abstract: Mass-analyzed threshold ionization (MATI) has been used to prepare phenol cations in selected vibrational states, including the ground state. Reactions of ground state C6H5OH+ with ND3, studied in a guided ion-beam apparatus, are reported, along with related ab initio calculations. This paper focuses on the energetics and product branching in the proton transfer (PT) channel. Based on thermochemistry in the literature, combined with calculations of the intracomplex PT barrier, PT was expected to make up a larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
56
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 24 publications
8
56
0
1
Order By: Relevance
“…The combination of excess energy from the 2-photon excitation process, ~100 kJ mol -1 , depending on the ionisation energy of the complex and the kinetic energy of the ejected photoelectron [39,40], with the energy released from the proton transfer reaction, ~50 kJ mol -1 , [43,44] Table Captions Table 1. Computed relative energies, dihedral angles and hydrogen bond distances/angles for protonated 1-phenyl ethylamine (PEA) and its complexes with the phenoxy radical: (i) MP2/6-311++G**//B3LYP/6-31+G*, (ii) B3LYP/6-31+G* optimisation.…”
Section: Hydrated Ephedrinementioning
confidence: 99%
“…The combination of excess energy from the 2-photon excitation process, ~100 kJ mol -1 , depending on the ionisation energy of the complex and the kinetic energy of the ejected photoelectron [39,40], with the energy released from the proton transfer reaction, ~50 kJ mol -1 , [43,44] Table Captions Table 1. Computed relative energies, dihedral angles and hydrogen bond distances/angles for protonated 1-phenyl ethylamine (PEA) and its complexes with the phenoxy radical: (i) MP2/6-311++G**//B3LYP/6-31+G*, (ii) B3LYP/6-31+G* optimisation.…”
Section: Hydrated Ephedrinementioning
confidence: 99%
“…They observed that the spectral trends were consistent with the proton affinity correlation and concluded that the intermolecular proton bond was mostly electrostatic in nature. However, because the phenoxy radical has a rather large proton affinity (873 kJ mol À1 ) [20], it appears useful to study a system that will more readily donate an acidic proton. In addition, the open-shell electronic configuration of the radical introduces a possible complication because of the low-lying electronically excited state.…”
Section: Introductionmentioning
confidence: 99%
“…MATI is, in principle, a general method. To date it has been used to rotationally select a number of diatomics [31,32] and to vibrationally select phenol cations [33].…”
Section: Experimental and Computational Methodsmentioning
confidence: 99%